A case report of eumycetoma in the thigh: an unusual presentation as a lump - Chitrambalam, Tharun Ganapathy; Sekhar, Sidhu; Panicker, Koshy Mathew; Sundaraj, Jeyakumar (International Surgery Journal, 2019)
Mycetoma is a chronic disease, which is endemic in tropical and subtropical countries. Mycetoma is a chronic subcutaneous infection caused by Actinomycetes or fungi. This infection results in a granulomatous inflammatory response in the deep dermis and subcutaneous tissue, which can extend to the underlying bone. Mycetoma is characterized by the formation of grains containing aggregates of the causative organisms that may be discharged onto the skin surface through multiple sinuses. Here we report an unusual presentation of eumycetoma in the thigh of a 41 year old male rural industrial worker hailing from South India.